From data to decision making in health : the evolution of a health mangement information system - Campbell, B (Royal Tropical Institute AmsterdamNL, 1996)
Presents a comprehensive picture of a Mangement Information System (MIS), including the design process, technical aspects of specific , MIS instruments and the potential for using information at various levels of the health system.